2012
DOI: 10.1093/jat/bks074
|View full text |Cite
|
Sign up to set email alerts
|

Deaths Involving 1,1-Difluoroethane at the San Diego County Medical Examiner's Office

Abstract: Intentional abuse of 1,1-difluoroethane has been reported to cause transient symptoms such as confusion, tremors, pulmonary irritation, loss of consciousness and, rarely, coma. In the last five years, 17 cases from the San Diego County Medical Examiner's Office showed the presence of 1,1-difluoroethane in postmortem tissues, and the gas was cited in the cause of death in 13 of those cases. Detected during routine ethanol screening, 1,1-difluoroethane was evaluated for concentrations in peripheral blood, centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Abuse of HFA 152a, found in canned air, has been linked to transient central nervous system symptoms including euphoria, confusion, and tremor. Furthermore, it is also linked to pulmonary irritation, asphyxia, cardiac arrhythmias, and death (43). However, short-term inhalation of 200 and 1,000 ppm HFA 152a for 2 h with light exercise did not prove to have significant central nervous system symptoms or pulmonary irritation in human subjects (44).…”
Section: Novel Propellantsmentioning
confidence: 99%
“…Abuse of HFA 152a, found in canned air, has been linked to transient central nervous system symptoms including euphoria, confusion, and tremor. Furthermore, it is also linked to pulmonary irritation, asphyxia, cardiac arrhythmias, and death (43). However, short-term inhalation of 200 and 1,000 ppm HFA 152a for 2 h with light exercise did not prove to have significant central nervous system symptoms or pulmonary irritation in human subjects (44).…”
Section: Novel Propellantsmentioning
confidence: 99%
“…For example, NMS Labs tests for DFE in blood by GC/MS and states that their reporting limit (LOQ) is 0.14 mg/L [ 44 ]. Notably, levels greater than 5.4 mg/L are judged by one published report to be evidence of intentional inhalation [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Florida State Medical Examiners Commission found that there were 49 statewide deaths caused by inhalants in 2018 of which 83% involved halogenated inhalants, especially DFE [ 24 ]. Reported acute health effects of DFE inhalation in nonfatal cases include auditory and visual hallucinations and delusions [ 25 ], mania with psychosis [ 26 ], disorientation, poor judgement and disinhibition, tremors, ataxia [ 23 ], generalized tonic clonic seizure activity [ 27 ], dyspnea on exertion [ 23 ], pulmonary irritation and cough [ 28 ], frostbite burns of skin [ 20 , 29 ], cutaneous burn injury by hydrofluoric acid from thermal degradation of DFE [ 30 ], cutaneous flame burns from fire ignition of DFE [ 30 ], angioedema [ 31 ], palpitations and irregular pulse, chest pain, pneumopericardium [ 29 ], cardiomyopathy [ 32 , 33 ], toxic myocarditis [ 23 ], nausea and vomiting, acute liver injury and fulminant hepatitis [ 23 , 33 , 34 ], rhabdomyolysis and acute renal failure [ 22 , 33 , 34 ]. Some reported long-term health effects include skeletal fluorosis [ 35 ] and possibly chronic kidney disease [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute on Drug Abuse reports that one in five American teens have used inhalants to get high. Experts estimate that there are several hundred deaths each year from inhalant abuse, although under-reporting is still a problem 4 5…”
Section: Discussionmentioning
confidence: 99%